2016
DOI: 10.1177/0956462416671087
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplement interactions with antiretrovirals: a systematic review

Abstract: Many patients who take antiretroviral drugs also take alternative therapies including dietary supplements. Some drug-supplement combinations may result in clinically meaningful interactions. We aimed to investigate the evidence for dietary supplement interactions with antiretrovirals. A systematic review was conducted using multiple resources including PubMed, Natural Medicine Comprehensive Database, The Review of Natural Products, and Google Scholar. All human studies or case reports evaluating an interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Although a low alcohol intake does not have negative effects on antiretroviral therapy adherence, it should be discouraged because of its harmful effects on quality of life and of the increased risk of hepatotoxicity. 15,[30][31] Therefore, professionals must address the recreational use of alcohol, advising patients not to interrupt drug treatment. 17 Another doubt was related to the use of dietary supplements and other drugs, which suggests the need to inform all people WhatsApp in the health of people with HIV Lima ICV, Galvão MTG, Pedrosa SC, Cunha GH, Costa AKB with HIV about these issues, with the purpose of preventing treatment flaws and/or side effects related to a possible interaction with antiretroviral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Although a low alcohol intake does not have negative effects on antiretroviral therapy adherence, it should be discouraged because of its harmful effects on quality of life and of the increased risk of hepatotoxicity. 15,[30][31] Therefore, professionals must address the recreational use of alcohol, advising patients not to interrupt drug treatment. 17 Another doubt was related to the use of dietary supplements and other drugs, which suggests the need to inform all people WhatsApp in the health of people with HIV Lima ICV, Galvão MTG, Pedrosa SC, Cunha GH, Costa AKB with HIV about these issues, with the purpose of preventing treatment flaws and/or side effects related to a possible interaction with antiretroviral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Results from systematic review published in 2017 show that the most frequently reported food supplement-antiretroviral medicine interactions in the literature from herbal origin are with St. John wort, ginkgo, milk thistle and cat's claw [14]. The proposed mechanism of action was examined mostly in pharmacokinetic studies and case-reports.…”
Section: Published Articles For Nutrition Recommendationmentioning
confidence: 99%
“…Because limiting the keywords by MeSH constraints may reduce the number of studies returned, searches were also executed without constraints by using the keywords “ginseng or Panax ginseng ginsenoside”, “ Ginkgo biloba ”, and “danggui or dong quai or Angelicae sinensis ” to retrieve additional review articles on HDIs to fulfill the additional criterion that at least one “systematic review article” every other year was retrieved to minimize the possibility of missing information. A total of fourteen “review” articles [11–24] published during the prior twenty years were collected.…”
Section: Construction and Contentmentioning
confidence: 99%